Faktor Yang Berhubungan Dengan Kelelahan Kerja Di PT. Maruki Internasional Indonesia Makassar (Window of Public Health Journal, 2025)
Fatigue is a combination of mental and physical function decline that reduces work enthusiasm, decreasing work effectiveness and efficiency. This study aims to determine the factors associated with work fatigue in workers at PT. Maruki International Indonesia in 2023. To achieve this, we conducted a quantitative study with a cross-sectional design. We used a total sampling technique, surveying all 64 workers in factory 1. Data were obtained using a questionnaire to measure various factors related to work fatigue. We then used univariate and bivariate analysis, including the chi-square test, to analyze the data. The results showed a relationship between age and work fatigue (p-value = 0.000